Double Burden of Malnutrition: Examining the Growth Profile and Coexistence of Undernutrition, Overweight, and Obesity among School-Aged Children and Adolescents in Urban and Rural Counties in Henan Province, China. (21st February 2020) - Zhou, Shengsheng; Ye, Bing; Fu, Pengyu; Li, Shan; Yuan, Pu; Yang, Li; Zhan, Xuan; Chao, Feng; Zhang, Shufang; Wang, Min Qi; Yan, Alice
Abstract : Objective . To examine the gender, age, and region of residence in the anthropometric and nutritional profiles of children and adolescents aged 6–18 in Henan Province, China's third most populous province. Design . This cross-sectional study of the China National Nutrition and Health survey (2010–2013) used a multistage cluster sampling technique. The sample included Chinese schoolchildren and adolescents aged 6 to 18 years (1, 660 boys and 1, 561 girls). Multiple logistic regression models were used to estimate the associations between sociodemographic correlates and overweight or obesity and stunting. Setting . Nine districts/counties in Henan Province. Participants . 3, 221 subjects completed the questionnaire. Sociodemographic information was obtained. Body weight and height were measured. Results . There were statistically significant regional differences in average height and weight for boys in all age groups. Girls followed the same trends except for height when 15–18 years old. The urban-rural residence differences were found in relation to prevalence of stunting and weight status. Subjects in poor rural areas (15.43%) and ordinary rural areas (15.34%) had higher rates of stunting compared to their urban counterparts. Prevalence of overweight or obesity was highest in big city areas (15.71%) and lowest in ordinary rural areas (6.37%). Being a boy (OR = 1.69, 95% CI = 1.314–2.143), living in a big city (OR = 2.10, 95% CI = 1.431–3.073), or in a small-medium city (OR = 2.28, CI = 1.606–3.247), or being in a younger age group was associated with being overweight or obese. In addition, being a boy, living in a big city, or in a small-medium city, or being younger in age meant they were less likely to be stunted. Conclusions . A substantial dual burden of malnutrition among children and adolescents in Henan Province was revealed. The urban-rural differences in nutritional status were found. Stunting was more prevalent in rural areas than in urban. In contrast, while the rising problem of childhood and adolescent obesity still exists in the big city, we also found a great spike in obesity in small-medium cities. Evidence also indicated that boys were more likely to be overweight or obese. Our findings suggest that nutrition education, as well as environmental and policy interventions, is needed to target specific geographic regions.